What are the differences between grab and track start? - Takeda, T.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
This study was intended to explain the difference in kinematic characteristics between a grab Start and a track Start in competitive swimming. The starting movement was modeled using a pendulum model. The take-off velocity (Vt) was resolved to a rotational component (Vrt) and an extensional component (Vet). The Vrt of the track Start was higher than that of the grab Start, although Vet of the grab start was higher than that of the track Start. A swirnmer with a track Start would be able to generate the high Vrt through the large moment of vertical force acting on the rear foot about the center of -gravity. In contrast, swimmers using the grab Start would be able to generate high Vet because the foot placement is in the same position on the front edge of the starting block. The take-off velocity of the grab Start is higher than that of track start because of the great Contribution of Vet to take-off velocity. In addition, the rotational displacement of the track start around the front edge of the starting block was small. Therefore, the track-start block time was shorter than that using the grab start.